2016
DOI: 10.1016/j.thromres.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography does not predict mortality in hemodynamically stable elderly patients with acute pulmonary embolism

Abstract: Background:The evidence on the prognostic value of transthoracic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…In our study, each of the 3 studied TTE findings was associated with 30‐day PE‐related mortality in unadjusted and adjusted models. A study of 529 patients with PE identified separate effects of PESI and TTE findings on 30‐day outcomes of patients with PE,3 while another recent study of 400 patients with PE by Hofmann et al did not find an independent association between TTE findings and outcomes 5. The association between RA enlargement and PE outcomes has been under recent investigation,13, 14 and may be potentially explained by right heart volume and pressure overload in the setting of acute PE.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, each of the 3 studied TTE findings was associated with 30‐day PE‐related mortality in unadjusted and adjusted models. A study of 529 patients with PE identified separate effects of PESI and TTE findings on 30‐day outcomes of patients with PE,3 while another recent study of 400 patients with PE by Hofmann et al did not find an independent association between TTE findings and outcomes 5. The association between RA enlargement and PE outcomes has been under recent investigation,13, 14 and may be potentially explained by right heart volume and pressure overload in the setting of acute PE.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies suggest that transthoracic echocardiography (TTE) could help in early risk stratification of patients with acute PE. Yet, the results have been inconsistent and the use of TTE in real life and its prognostic value have not been consistently studied 3, 4, 5, 6. We used the data from the RIETE (Registro Informatizado Enfermedad TromboEmbolica) registry to report the real‐world use and predictors of early TTE (within the first 72 hours from diagnosis) in patients with PE, and to explore the association between some of the main TTE findings and 30‐day PE‐related mortality in unadjusted and adjusted analyses.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis done on 3,395 patients admitted with PE revealed a twofold increase in mortality, but sub-analysis on normotensive patients correlated poorly with mortality [13]. Similar results were seen in a study done in 400 patients older than 65 years of age, which showed that RVD in APE was not associated with poor outcomes [12]. Our study supports these findings that normotensive patients with APE are not at increased risk for 30-day mortality, although hemodynamic instability with RVD is associated with increased mortality.…”
Section: Discussionmentioning
confidence: 58%
“…The prevalence of RVD varies from 30% to 80% depending on the definition used [12]. The lack of standard criteria is the reason for the wide variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation